ANALISIS GAYA BAHASA ALITERASI DAN ANAFORA PADA KUMPULAN PUISI KAMU TIDAK ISTIMEWA KARYA NATASHA RIZKY - Nur Fadillah; Irna Fitriana; Muhammad Asdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and analyze the figurative language of alliteration and anaphora in Natasha Rizky's poetry collection "Kamu Tidak Istimewa." This study uses a qualitative descriptive approach, with data collection techniques using documentation and analysis tables. The data are documents, namely poetry collections containing alliteration and anaphora. The results are expected to demonstrate that alliteration is used to create rhythm and musicality in the poetry, while anaphora is used to emphasize feelings and strengthen the poet's intended message. Thus, the use of these two figurative language styles enriches the meaning and beauty of the poetry in "Kamu Tidak Istimewa." This research contributes to the understanding of linguistic techniques used in modern poetry and broadens insight into contemporary Indonesian literature.